ВИКОРИСТАННЯ АКТИВНИХ МЕТОДІВ НАВЧАННЯ ЩОДО ПРОБЛЕМИ ФОРМУВАННЯ АНСАМБЛЕВОЇ НАВИЧКИ СТУДЕНТІВ МУЗИЧНО-ПЕДАГОГІЧНИХ ФАКУЛЬТЕТІВ (Педагогіка вищої та середньої школи, 2009)
The article pays special attention to the need to use active teaching methods in the process of forming the professionally necessary ensemble skills of the future music teacher.